2021
DOI: 10.22266/ijies2021.0430.21
|View full text |Cite
|
Sign up to set email alerts
|

Engagement Detection through Facial Emotional Recognition Using a Shallow Residual Convolutional Neural Networks

Abstract: Online teaching and learning has recently turned out to be the order of the day, where majority of the learners undergo courses and trainings over the new environment. Learning through these platforms have created a requirement to understand if the learner is interested or not. Detecting engagement of the learners have sought increased attention to create learner centric models that can enhance the teaching and learning experience. The learner will over a period of time in the platform, tend to expose various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Based on the literature review, it has been discovered that the majority of researchers focusing on academic affective states utilized the DAiSEE dataset to train their models in order to determine student engagement in learning environments [5,6,8,9,12,36,37]. A commonly noted challenge among researchers working with the DAiSEE dataset is the issue of dataset imbalance [10,14,30,37].…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature review, it has been discovered that the majority of researchers focusing on academic affective states utilized the DAiSEE dataset to train their models in order to determine student engagement in learning environments [5,6,8,9,12,36,37]. A commonly noted challenge among researchers working with the DAiSEE dataset is the issue of dataset imbalance [10,14,30,37].…”
Section: Datasetmentioning
confidence: 99%
“…In the class time, students show positive expressions or emotions such as attention, engagement, and understanding to indicate that he or she is comprehending the material. They express Negative emotions such as confusion, frustration, or boredom to indicate that the student is struggling and may need additional support or clarification [6,7]. Table 1.1 gives the cases when students deliver either positive or negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [28], Whitehill et al showed that automated engagement detectors perform with comparable accuracy to humans. In [3] [19,21,23], authors used models which are based on Convolutional Neural Networks (CNN) and Residual Networks (ResNet) [12]. All the works above considered the engagement detection problem as a multi-class classification problem.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, some more methods are developed with the aim of robustness in FER by applying a deep learning-based classifier. M. M. Thiruthuvanathan, and B. Krishnan [41,42] adopted Convolutional Neural Networks (CNNs) and enabled them with residual components to enhance the learning rate of the network. They employed this model to classify classroom engagement through facial expression recognition.…”
Section: Literature Surveymentioning
confidence: 99%